A molecular hydrodynamic study of marine based non-digestible fibre polysaccharides considered for use in health products - Almutairi, Fahad Mohammed (2015)
Marine polysaccharides have been widely used as a source of nutritional supplement for various therapeutic applications. Uncertainties and significant gaps in our knowledge about the macromolecular properties of these substances have limited their use particularly in the pharmaceutical industries where a detailed understanding of materials used for therapies are essential. Therefore, in order to increase our awareness so as to develop better healthcare and therapies against common diseases it is important to establish a better understanding of molecular properties and interactions. The focus of this thesis has been on carrageenans – materials which have arguably been the greatest source of controversy and disagreement in the past in terms of properties – chitosan and alginate and their relations with other substances (mucins, DNA and other polysaccharides).